2019
DOI: 10.1186/s43042-019-0028-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of Egyptian colorectal cancer patients regarding somatic genetic mutations especially in KRAS gene and microsatellite instability status: a pilot study

Abstract: Background: Colorectal cancer (CRC) is the third most common cause of cancer-related deaths which contributes to a significant public health problem worldwide with 1.8 million new cases and almost 861,000 deaths in 2018 according to the World Health Organization. It exhibits 7.4% of all diagnosed cancer cases in the region of the Middle East and North Africa. Molecular changes that happen in CRCs are chromosomal instability, microsatellite instability (MSI), and CpG island methylator phenotype. The human RAS f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…Matching with a recent study by Kassem et al [19] on the Egyptian CRC patients, we found ve TP53 somatic mutations; c.1024C > T, c.844C > T, c.743G > A, c.524G > A and 215C > G in our CRC group which might reveal that such variants are Egyptian speci c and explain their contribution in colon cancer disease progression as a driver mutation in tumor development.…”
Section: Discussionsupporting
confidence: 89%
“…Matching with a recent study by Kassem et al [19] on the Egyptian CRC patients, we found ve TP53 somatic mutations; c.1024C > T, c.844C > T, c.743G > A, c.524G > A and 215C > G in our CRC group which might reveal that such variants are Egyptian speci c and explain their contribution in colon cancer disease progression as a driver mutation in tumor development.…”
Section: Discussionsupporting
confidence: 89%
“…We previously reported a lower frequency of BRAF mutations (20.45%) in this MSI-CRC cohort [6], similar to what has been reported in China [47][48][49]. This is unlike a common dogma in which KRAS mutation is more associated with MSS while BRAF mutation is associated with MSI [50,51]. We also observed the concomitant KRAS and BRAF mutation on 5.73% of total CRC cases.…”
Section: Discussionsupporting
confidence: 88%
“…The following quality control parameters and thresholds were used for each step of RNA-seq: RNA integrity number, >7.0 39 ; DV200, !70% 40 ; library fragment size, 270 to 370 bp 41 ; cluster passing filter, !80%; percentage of bases with a quality score !30, !80%; sequencing error rate, <1% 42,43 ; percentage of reads after Q10 trimming, !90%; percentage of uniquely mapped reads, !70%; duplication rate, 70%; on-target rate with !1Â coverage, !90%; and an on-target rate with !100Â coverage, !50%. 39 RNA integrity number DV200 and library fragment size were analyzed using a 4200 TapeStation system (Agilent Technologies).…”
Section: Filtering and Prioritization Of Fusion Candidatesmentioning
confidence: 99%